Ni/SBA-15 catalysts for CO methanation: effects of V, Ce, and Zr promoters. Issue 117 (9th November 2015) - Li, Haidong; Ren, Jun; Qin, Xiang; Qin, Zhifeng; Lin, Jianying; Li, Zhong
Abstract : The addition of promoter species to 10Ni/SBA-15 catalysts is of significant importance for the CO methanation reaction. Abstract : Ni/SBA-15 catalysts with various promoters (V, Ce, and Zr) were prepared by an ultrasonic coimpregnation method and used in CO methanation. The addition of promoters played a significant role in improving the catalytic activity of the Ni/SBA-15 catalyst. This improvement could be explained by changes in the valences of the V and Ce promoter species through an oxidation–reduction shift cycle process (M x + ↔ M y +, M = V, Ce), which could trigger electron transfer. This transfer enhanced the electron density of active Ni species and promoted CO dissociation. The Zr promoter could produce oxygen vacancies during calcination and reduction, thereby increasing the ability of CO to adsorb and dissociate. In addition, the formation of a Si–O–M bond (M = Zr, Ce, V) increased the interaction between the active species and support, which facilitated CO methanation. Under 1.0 MPa and a WHSV of 15 000 mL g −1 h −1, 10Ni–5V/SBA-15 exhibited the best catalytic performance (99.9% CO conversion; 95.5% CH4 selectivity).